Translation Strategies Used by Tiffany Tsao in Rendering Culture-Specific Items in Dewi Lestari’s “Paper Boats” - Ifadloh, Nur; Nufus, Zahratun; Haura, Raudhatul; Aulia, Syairatul; Sari, Yustika Desta (SALEE: Study of Applied Linguistics and English Education, 2024)
To This study aims to reveal the translation strategy used by Tiffany Tsao in rendering of CSIs in the novel “Paper Boats” by Dewi Lestari based on Baker's theory. This study is descriptive qualitative research. The data consist of lingual units, in the form of words or phrases, which contain culture-specific items. The source of data is taken from “Paper Boats” novel by Dewi Lestari that translated by Tiffany Tsao. The data were collected through observation and by taking notes and analyzed using the equivalent and referential methods. The findings show that there are six translation strategies used by Tiffani Tsao in rendering CSIs in Dewi Lestari's paper boats novel. Superordinate (translation by a more general word) becomes the most dominant translation strategies in rendering CSIs in this novel followed by translation using a loan word or loan word plus explanation, translation by cultural substitution, translation by paraphrase using related words, translation by paraphrase using unrelated words and translation by omission.